(untitled) (Research, Society and Development, 2019)
This work has as objective the development of an embedded platform that can guide the first steps of a student in the area of embedded programming. Describes the development of a package of software to support the learning of embedded programming, mainly using real time operating systems, as well as documents the initial activities of the PQDB platform (Pão de Queijo Development Board). The development techniques to embedded are not the same applied to desktops and mainframes. There are memory restrictions, limited processing capacity, input and output device management, various communication protocols, this because each embedded system is a different project that may not follow patterns, in this way the knowledge of the hardware is essential to the software design that will be embedded in the device. Thus, we studied the fundamentals of microprocessed and microcontrolled systems, general characteristics of operating systems, real-time systems, and some relevant features of software engineering. The implementations were performed with the Kinetis Design Studio 3 ® IDE, the FreeRTOS ® operating system, the NXP FRDM-K64F development board and the Pão de Queijo Development Board (PQDB) that was designed and developed in the Federal University of Itajubá. In this work we present how this board assists student learning in embedded software, presenting a quick guide to how to port the FreeRTOS in addition to developing libraries and drivers to communicate with peripherals. It is concluded that the use of a pre-assembled board simplifies the understanding of the student as it removes layers of complexity from the learning activity. The same happens with the use of a real time operating system, that abstract the time constraints questions to critical systems. It was also noted that the PQDB board offers several features that, if well exploited, guarantee a great start in the area of development of embedded software.